2007
DOI: 10.1088/0960-1317/17/10/n01
|View full text |Cite
|
Sign up to set email alerts
|

Fast prototyping using a dry film photoresist: microfabrication of soft-lithography masters for microfluidic structures

Abstract: Etertec HQ-6100 dry film photoresist was used in this work to fabricate soft-lithography masters applied to microfluidic applications. We demonstrated that the use of this photoresist was a convenient alternative to conventional microfabrication approaches based on DRIE and liquid photoresists for fast-prototyping of microfluidic structures. Our method was at least two times faster than conventional processes and required limited investment for equipments. Finally, this approach was applied to the design and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 18 publications
(21 reference statements)
0
61
0
Order By: Relevance
“…The microfluidic devices are prepared using dry-film soft lithography techniques (41). The channels are etched in PDMS and bonded on a PDMS-covered glass slide.…”
Section: Methodsmentioning
confidence: 99%
“…The microfluidic devices are prepared using dry-film soft lithography techniques (41). The channels are etched in PDMS and bonded on a PDMS-covered glass slide.…”
Section: Methodsmentioning
confidence: 99%
“…First, a PDMS microchannel was fabricated by replica molding using a dry film photoresist. 23 Then, a thin PDMS layer was coated onto the magnetic film surface to facilitate microchannel bonding by air plasma and to provide a biocompatible surface for cell attraction. This layer also serves to protect the magnetic film from corrosion.…”
Section: Microfluidic Integrationmentioning
confidence: 99%
“…We have found that we can produce features down to as small as 40 µm in width (see Figure ? ?) without a collimated light source - (Stephan et al, 2007) could get no smaller than 200 µm without a collimated light source. Recognising the potential for our DFR protocols to be useful for others we have included them in the Appendix.…”
Section: Fabricationmentioning
confidence: 99%